Economic Cooperation Between The European Union And Japan - Drzymała, Agnieszka (Comparative Economic Research. Central and Eastern Europe, 2017)
The aim of the paper is to show the history of economic relations between the European Union and Japan. This economy is very important to the EU and the countries of the EU are interested in further deepening areas of cooperation. Therefore it seems important to indicate the political will to continue mutual economic relations through the signing of contracts and bilateral agreements, as well as meetings at various levels, including SPA and EPA negotiations and summits. The course of the current economic cooperation will be shown through trade volume and foreign direct investment outflows from the European Union to Japan.